PENGARUH INSENTIF DAN KOMUNIKASI TERHADAP MOTIVASI DAN PRESTASI KERJA KARYAWAN PT. CAPELLA DINAMIK NUSANTARA PEKANBARU - Melsi Novita Sari; Machasin '; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this study was to look at the influence of Incentive and Communication on Motivation and Work Peformance PT. Capella Dinamik Nusantara Pekanbaru. The population in this study amounted PT. Capella Dinamik Nusantara Pekanbaru 102 employees. While the sampling technique is done by census method. Data analysis was performed using the path analiysis processed with spss version 18.0. Based on the survey results revealed that there are significant indirect incentives to work achievement through work motivation and there is no direct influence on the Job Performance Communication Working through work motivation. This means that work can strengthen the motivation variable incentive effect and work towards achievement of communication Employee. Companies should consider factors that affect employee performance by increasing employee motivation at work , as well as the incentives and pay attention to the communication that exists among employees so that employee performance can be improved.Keywords : Incentive, Communication, Motivation and Work Peformance